A phase 3, multicenter, randomized, allopurinol‐controlled study assessing the safety and efficacy of oral febuxostat in Chinese gout patients with hyperuricemia. (27th May 2015) - Xu, Shaoyong; Liu, Xiangyang; Ming, Jie; Chen, Shenren; Wang, Yangang; Liu, Xiumei; Liu, Hong; Peng, Yongde; Wang, Jianqin; Lin, Jinying; Ji, Haiwang; Liu, Bin; et al.
Abstract: Aim: To compare the efficiency and safety of febuxostat with those of allopurinol in Chinese patients with gout and hyperuricemia. Methods: The trial which was conducted at 13 centers in China during 2011–2013 included a 2‐week run‐in and a 24‐week treatment period. A total of 504 eligible participants with gout and with serum urate ≥ 480 μmol/L were randomly assigned 1 : 1 : 1 to febuxostat 40 mg/day, febuxostat 80 mg/day and allopurinol 300 mg/day groups. The primary efficacy endpoint was the percentage of subjects whose last three serum urate levels were < 360 μmol/L. Results: The primary efficacy endpoint was reached by 33.5% of subjects taking febuxostat 80 mg/day, 22.5% of those taking febuxostat 40 mg/day and 17.0% of those taking allopurinol 300 mg/day ( P  <   0.001 for the comparison between febuxostat 80 mg/day and allopurinol 300 mg/day groups; P  =   0.216 for the comparison between febuxostat 40 mg/day and allopurinol 300 mg/day groups). The incidence of gout flare was relatively high in each group during the first 8 weeks and gradually decreased thereafter. There was no statistically significant difference between the three groups ( P  >   0.05). The incidence of adverse events was similar in the three treatment groups. The most frequent treatment‐related adverse events were liver function test abnormalities. Conclusions: Febuxostat 80 mg/day had superior urate‐lowering efficacy to that of febuxostat 40 mg/day or allopurinol 300 mg/day, which was comparable in Chinese gout patients with hyperuricemia. Febuxostat, at a daily dose of 40 or 80 mg, was safe and well tolerated.